The psychology of political communicators how politicians, culture, and the media construct and shape public discourse - Feldman, Ofer 1954-; Zmerli, Sonja 1966- (New York, NY Routledge, 2019)
"In this timely study, Ofer Feldman, Sonja Zmerli and their team of experts shed light on the multiple ways communication affects political behavior and attitudes. Written for students and scholars alike, The Psychology of Political Communicators uses examples from the U.S., Europe, Asia and the Middle East to examine the nature, characteristics, content and the reception of communication in three major areas of discourse: - The style and nature of language used by political actors in the national and international arenas - The discourse used in nationalist populist movements and during negative campaigns - The rhetoric of the media as it tries to frame politics, political events and political actors Collectively, the essays form a solid foundation on which to understand the different roles language plays in the conduct of politics, the way in which these roles are performed in various situations in different societies and cultures, and the political outcomes of verbal behavior. This book will be of interest to scholars and students of political psychology and communication studies"-- Provided by publisher.
The new American electoral politics: how invited behavior and reality tv explain Donald Trump's victory / Michael Alan Krasner -- Political communicators and control in political interviews in Japanese television: a comparative study and the effect of culture / Ofer Feldman and Ken Kinoshita -- Comparing Japanese and U.S. leaders' communication: the construction of meaning in addresses to the United Nations General Assembly / Sarah Tanke -- They caused our crisis! the contents and effects of populist communication: evidence from the Netherlands / Michael Hameleers -- Populism in self-directed and mediated communication: the case of the five star movement in the 2013 Italian electoral campaign / Cristina Cremonesi -- Fighting with fire: negative campaigning in the 2015 U.K. general election campaign as reported by the print media / Annemarie Walter -- Representations of televised debates in the press and their influence on political candidates: the cases of Spain, the U.K., and the U.S. / Laura Pâerez Rastrilla -- Non-systemic factors underlying rapid change in gender-biased media framing of female politicians: 2009 and 2013 Israeli newspaper election coverage / Gilad Greenwald and Sam Lehman-Wilzig -- Old traps and new prospects: gendered media images of leading female politicians in Germany as evidence for a contested modernization of gender knowledge / Dorothee Beck -- "Men prefer redheads": media framing of polls and its effect on trust in media / Pazit Ben-Nun Bloom and Marie Courtemanche -- Media ownership: propositions for an extended research agenda / Sonja Zmerli.
Includes bibliographical references and index.
Keywords: Communication in politics; Mass media -- Political aspects; Political psychology